Essentials of economics - N. Gregory Mankiw (Australia : Cengage Learning, 2021)
Now you can master the essential principles of economics with the help of the most popular economics series that's trusted by students like you worldwide. Mankiw$1 (Bs ESSENTIALS OF ECONOMICS, 9E uses a concise, inviting presentation that emphasizes only the material that helps you better understand the world and economy in which you live. You learn to become a more astute participant in today's economy with a strong understanding of both the potential and limits of economic policy. The latest relevant examples bring economic principles to life. Acclaimed author Gregory Mankiw explains, "I tried to put myself in the position of someone seeing economics for the first time. My goal is to emphasize the material that students should and do find interesting about the study of the economy." To help you further master key principles of economics, powerful student-focused digital resources are available in the leading MindTap digital learning and homework solution.s
Keywords: Economics; Essentials